Kal?m Amr: The Literal And Figurative Meanings - Lisa Natalia; Mohammad Harjum; M. Fatkhul Ulum (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
nt This study, entitled “Kal?m Amr: The Literal and Figurative Meanings”, investigates the linguistic and rhetorical dimensions of Kal?m Amr—imperative speech in Arabic—as discussed in the field of ‘Ilm al-Bal?ghah. The issue is significant because the Qur’an, as the pinnacle of Arabic eloquence, employs Kal?m Amr not only to express commands but also to convey deeper meanings such as advice, threat, or supplication. Previous research has tended to focus on grammatical or syntactical elements, leaving a conceptual gap in exploring semantic variations and contextual interpretation between ?aq?q? (literal) and maj?z?y (figurative) meanings. This study aims to fill that gap by analyzing the contextual shifts in meaning and communicative purposes behind imperative forms in Qur’anic discourse Using a qualitative-descriptive and library-based method, this study examines classical and contemporary Arabic rhetorical works, including key texts such as the Qur'an, Hadith, and classical tafsir. The data was collected through a documentation study, where various written sources, including books, journal articles, and religious texts, were gathered and reviewed. Data analysis was performed using thematic and comparative approaches, focusing on the shifts in meaning and communicative purposes behind imperative forms in Qur’anic discourse. To ensure the validity of the findings, textual indicators (qar?’in) were identified and cross-checked with multiple sources to account for potential variations in interpretation. This triangulation method helped to validate the interpretations and strengthen the study's conclusions.The findings reveal that Kal?m Amr extends beyond literal instruction, encompassing diverse rhetorical functions shaped by social, theological, and communicative contexts. The study concludes that understanding the distinction between ?aq?q? and maj?z?y meanings enriches the interpretative depth of Qur’anic language and enhances appreciation of its aesthetic and spiritual eloquence.